2015
DOI: 10.1063/1.4916709
|View full text |Cite
|
Sign up to set email alerts
|

The discrete Fourier transform algorithm for determining decay constants—Implementation using a field programmable gate array

Abstract: Cavity ringdown spectroscopy (CRDS) uses the exponential decay constant of light exiting a high-finesse resonance cavity to determine analyte concentration, typically via absorption. We present a high-throughput data acquisition system that determines the decay constant in near real time using the discrete Fourier transform algorithm on a field programmable gate array (FPGA). A commercially available, high-speed, high-resolution, analog-to-digital converter evaluation board system is used as the platform for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…For CRD, the APD signal is sent to an oscilloscope (PicoScope 2000 A, Pico Technology, St. Neots, Cambridgeshire, UK), which acquires the decays and stores them in an on-board buffer before sending a block of waveforms to LabVIEW. Once in LabVIEW, the decays are co-added and fit to an exponential function using the discrete Fourier transform method (Mazurenka et al 2005;Everest and Atkinson 2008;Bostrom et al 2015).…”
Section: Electronics and Data Acquisitionmentioning
confidence: 99%
“…For CRD, the APD signal is sent to an oscilloscope (PicoScope 2000 A, Pico Technology, St. Neots, Cambridgeshire, UK), which acquires the decays and stores them in an on-board buffer before sending a block of waveforms to LabVIEW. Once in LabVIEW, the decays are co-added and fit to an exponential function using the discrete Fourier transform method (Mazurenka et al 2005;Everest and Atkinson 2008;Bostrom et al 2015).…”
Section: Electronics and Data Acquisitionmentioning
confidence: 99%
“…In previous work [43], it was shown that non-iterative FFT methods have a 200 µs calculation time and that a least squares fitting algorithm requires > 1 ms of calculation time to analyse decaying oscillations of the same length that we consider in this paper using similar computational facilities to the systems used in this present work. Others have shown FPGA-based FFT algorithms for determining the decay constant of decaying signals with analysis rates of 4.4 kHz [40]. Here, we show that trained autoencoder networks are able to analyse incoming signals significantly faster than previously reported methods.…”
Section: B Decaying Oscillationsmentioning
confidence: 52%
“…Different time-and frequency-based computational methods for rapid parameter estimation have been demonstrated, and evaluated, for cavity ring-down (CRD) spectroscopy methods [37][38][39]. Among those, Fourier-transform methods on a field programmable gate arrays (FPGA) have demonstrated data-time analysis rates as high as 4.4 kHz [40]. Several works discuss timeand frequency-domain analysis algorithms for damped sinusoidal signals [41,42] and we recently published a comparative study of three specific analysis methods of discretely sampled damped sinusoidal signals in terms of their speed, and attainable accuracy and precision [43].…”
mentioning
confidence: 99%
“…Time-and frequency-based computational methodologies for rapid parameter estimation have been developed within the context of CRD spectroscopy, and these have been evaluated and compared in terms of their speed and precision [27][28][29]. Most notably, Fourier transform methods have been implemented on FPGAs for fast analysis of exponentially decaying signals [30], with demonstrated analysis rates as high as 4.4 kHz [31]. However, while several works discuss the performance of various time-and frequency-domain analysis algorithms for damped sinusoidal signals [32,33], a direct comparison between their attainable precision and computational speed is currently missing.…”
Section: Introductionmentioning
confidence: 99%